Κτίστας θεωρεῖς. Wer ist der zivile Würdenträger auf dem Stiftermosaik in der Demetrios-Kirche in Thessaloniki? - FOURLAS, Benjamin (Byzantina Symmeikta, 2011)
WHO IS THE CIVIL DIGNITARY ON THE MOSAIC OF THE DONORS IN THE CHURCH OF ST DEMETRIOS IN THESSALONIKI? This paper focuses on the analysis of the insignia, the portrait and the so-called square nimbus in order to clarify the identity of the anonymous civil dignitary depicted in the famous 7th century mosaic of the donors in the church of St Demetrios in Thessaloniki. It is argued that he is not (as often supposed) the founder of the church, the praetorian prefect of Illyricum Leontios, but rather a contemporary donor of the mid-7th century who contributed to the rebuilding of the church after a fire damaged the building about 620/30. His garment and his insignia do not fit to those of a praetorian prefect but most likely represent the highest senatorial dignity in the 7th century, namely that of an honorary consul (ἀπὸ ὑπάτων or ὕπατος). This does not exclude the possibility that he did hold the office of the prefect of eastern Illyricum (respectively of Thessaloniki) as well. The mentioning of the name Leo in the mosaic inscription pertaining to the rebuilding after the fire follows a common epigraphic habit in building inscriptions that refers to the authority responsible to approve the execution of the project. This Leo is often assumed to be the same person as the civil dignitary. Although this conclusion is generally possible it has to remain hypothetical.